Sodium-ion battery hard carbon negative electrode material and preparation process thereof
Through the pre-carbonization-pore-making-high-temperature carbonization process and the organic zinc acid salt additive method, the problem of unsatisfactory capacity and Coulomb efficiency of sodium ion batteries is solved, and higher sodium storage capacity and electrochemical performance are achieved, which is suitable for commercial applications of sodium ion batteries.
Patent Information
- Application Number
- CN202411950876.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
AI Technical Summary
The capacity of existing sodium ion battery hard carbon anode materials and the Coulomb efficiency for the first charging and discharging are not ideal, and it is difficult to meet the requirements of sodium ion battery to improve battery life, cycle stability, energy density and rate performance.
The carbon powder precursor is treated by pre-carbonization-pore-high temperature carbonization process. By adding zinc-organic acid salt additives, oxidative cross-linking and rearrangement and departure of carbon and oxygen functional groups occur during the pre-carbonization process, forming a relatively stable carbon-based mesh structure, thereby regulating the pore structure and degree of graphitization of carbon materials.
It improves the reversible capacity of sodium storage and first-time Coulomb efficiency of hard carbon anode materials of sodium ion batteries, improves electrochemical performance, and is suitable for promotion and application.
Smart Images

Figure CN119706804A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion battery materials, and in particular relates to a sodium ion battery hard carbon negative electrode material and a preparation process thereof. Background Art
[0002] Sodium-ion battery is a new type of secondary rechargeable battery. Compared with traditional lithium-ion batteries, sodium-ion batteries have their own unique advantages. First, sodium is more abundant in reserves, which makes the cost of sodium-ion batteries lower. Second, sodium is widely distributed and easy to obtain. In addition, sodium-ion batteries perform better at low temperatures and can better meet the use of cold climate conditions. Therefore, sodium-ion batteries have become a hot area for the development of new energy, and the development of low-cost, high-performance sodium-ion batteries is an important research direction in this field.
[0003] Despite the above advantages of sodium-ion batteries, there are still some challenges, such as improving battery life and cycle stability, as well as improving energy density and rate performance. The electrochemical performance of sodium-ion batteries is mainly determined by the characteristics of the positive and negative electrode materials. Among the negative electrode materials of sodium-ion batteries, hard carbon materials are considered to be the most commercially promising negative electrode materials due to their low sodium ion insertion / extraction potential and simple preparation methods. However, the capacity and first full coulombic efficiency of hard carbon materials are still not ideal.
[0004] Therefore, exploring and developing hard carbon negative electrode materials with high capacity and high initial efficiency is crucial for the development of sodium-ion batteries.
[0005] The patent material with announcement number CN116969442A discloses a method for preparing a high-capacity asphalt-based hard carbon sodium-ion battery negative electrode material. The asphalt-based hard carbon material is prepared by adopting a pre-oxidation-pre-carbonization combined treatment and a zinc salt catalysis method. The invention uses a further pre-carbonization process on the asphalt raw materials after pre-oxidation to reduce the surface defects of the final hard carbon product and improve the initial efficiency and capacity of the sodium-ion battery. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a sodium ion battery hard carbon negative electrode material and a preparation process thereof.
[0007] The present invention is achieved through the following technical solutions.
[0008] The present invention provides a process for preparing a hard carbon negative electrode material for a sodium ion battery, comprising the following steps:
[0009] 1) preparing a precursor mixed solution;
[0010] 2) drying the solution in step 1) to obtain a precursor powder;
[0011] 3) Pre-carbonization: pre-carbonizing the precursor powder in step 2) at a medium to low temperature;
[0012] 4) Pickling and drying: pickling, washing and drying the material in step 3);
[0013] 5) Carbonization: The material pre-carbonized in step 4) is carbonized at high temperature and then cooled to room temperature to obtain a hard carbon material.
[0014] Preferably, the step 1) comprises: uniformly mixing an organic acid zinc salt and polysaccharide biomass to form a precursor material, wherein the mixture is uniformly dispersed, and the carbon source of the organic acid salt comprises any one or more of zinc citrate, zinc oxalate, zinc gluconate, zinc acetate and zinc lactate.
[0015] Preferably, the mixing is carried out in the form of aqueous solution dispersion, the aqueous solution dispersion includes magnetic stirring for 30 to 120 minutes, and the polysaccharide biomass includes starch or glucose.
[0016] Preferably, the drying method used in step 2) includes one or more of freeze drying, spray drying, and thermal evaporation, and the drying time is 6 to 24 hours. Freeze drying includes freeze drying at -40 to -15°C for 11 to 30 hours. In step 3), the pre-carbonization temperature is 400 to 1000°C, the heating rate is 0.5 to 5°C / min, and the carbonization time is 0.5 to 2 hours.
[0017] Preferably, the pickling solution in step 4) is one or more of hydrochloric acid, sulfuric acid and nitric acid, with a concentration of 0.05 to 1 mol / L, and the pickling time is 0.5 to 2 h.
[0018] Preferably, the atmosphere in the high-temperature carbonization in step 5) is argon, the carbonization temperature is 1000-1800° C., the heating rate is 0.5-10° C. / min, and the insulation time is 1-10 h.
[0019] Preferably, in step 4), the drying is carried out at 90-120° C. for 6-11 hours.
[0020] Preferably, the mixing ratio of the organic acid zinc salt to the polysaccharide biomass is 1:1-4.
[0021] A sodium ion battery hard carbon negative electrode material is prepared by the above preparation process.
[0022] A sodium ion battery comprises the above-mentioned sodium ion battery hard carbon negative electrode material.
[0023] The beneficial effects of the present invention are:
[0024] The method of the present invention is a method for preparing a starch-based hard carbon negative electrode material. A pre-carbonization-pore-forming-high-temperature carbonization process is used to treat a carbon powder precursor. By adding an organic acid zinc salt additive, oxidative cross-linking occurs during the pre-carbonization process, and rearrangement and departure of carbon oxygen functional groups occur, thereby obtaining a relatively stable carbon-based network structure. The pre-carbonization process can inhibit foaming during starch pyrolysis and improve the carbon yield of the final hard carbon. The pore structure of the carbon material can be further regulated by removing the template in combination with high-temperature carbonization, and a more stable structure that is beneficial to improving electrochemical performance is formed during the subsequent high-temperature carbonization at 1000°C to 1600°C. At the same time, re-carbonization at 1000°C to 1600°C can increase the degree of graphitization of the hard carbon material, limit defects, and increase the specific capacity of the sodium ion battery. This can further improve the sodium storage reversible capacity of the prepared hard carbon.
[0025] The material of the present invention is simple to prepare, highly operable, low in cost, and has obvious effects. The hard carbon negative electrode material prepared by the present invention has a reversible capacity of up to 370 mAh / g at 0.1C and an initial coulombic efficiency of 89%, has great potential commercial value, and is suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of the hard carbon negative electrode material prepared in Example 1 of the present invention;
[0027] Figure 2 TEM image of the hard carbon negative electrode material prepared in Example 1 of the present invention;
[0028] Figure 3 The XRD spectrum of the hard carbon negative electrode material prepared in Example 1 of the present invention;
[0029] Figure 4 The charge and discharge curve of the first cycle of a sodium ion battery assembled with the hard carbon negative electrode material prepared in Example 1 of the present invention as the negative electrode material of a sodium ion battery at a current density of 0.1C; DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described below, but the scope of protection claimed is not limited to the description.
[0031] like Figures 1 to 4 As shown, a preparation process of a hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0032] 1) preparing a precursor mixed solution;
[0033] 2) drying the solution in step 1) to obtain a precursor powder;
[0034] 3) Pre-carbonization: pre-carbonizing the precursor powder in step 2) at a medium to low temperature;
[0035] 4) Pickling and drying: pickling, washing and drying the material in step 3);
[0036] 5) Carbonization: The material pre-carbonized in step 4) is carbonized at high temperature and then cooled to room temperature to obtain a hard carbon material.
[0037] The step 1) includes: uniformly mixing organic acid zinc salt and polysaccharide biomass to form a precursor material, mixing and dispersing the mixture uniformly, wherein the carbon source of the organic acid salt includes any one or more of zinc citrate, zinc oxalate, zinc gluconate, zinc acetate and zinc lactate.
[0038] The mixing is carried out in the form of aqueous solution dispersion, wherein the aqueous solution dispersion includes magnetic stirring for 30 to 120 minutes, and the polysaccharide biomass includes starch and glucose.
[0039] The drying method used in the step 2) includes one or more of freeze drying, spray drying, and thermal evaporation, and the drying time is 6 to 24 hours. Freeze drying includes freeze drying at -40 to -15°C for 11 to 30 hours. The pre-carbonization temperature in the step 3) is 400 to 1000°C, the heating rate is 0.5 to 5°C / min, and the carbonization time is 0.5 to 2 hours.
[0040] The pickling solution in step 4) is one or more of hydrochloric acid, sulfuric acid and nitric acid, with a concentration of 0.05 to 1 mol / L, and the pickling time is 0.5 to 2 hours.
[0041] The atmosphere in the high-temperature carbonization in step 5) is argon, the carbonization temperature is 1000-1800° C., the heating rate is 0.5-10° C. / min, and the insulation time is 1-10 h.
[0042] In the step 4), the mixture is dried at 90-120° C. for 6-11 hours.
[0043] The mixing ratio of the organic acid zinc salt to the polysaccharide biomass is 1:1-4.
[0044] A sodium ion battery hard carbon negative electrode material is prepared by the above preparation process.
[0045] A sodium ion battery comprises the above-mentioned sodium ion battery hard carbon negative electrode material.
[0046] Embodiment 1:
[0047] A preparation process of a hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0048] 1) Precursor mixing: zinc gluconate and starch are dispersed and mixed in an aqueous solution in a mass ratio of 1:4, and magnetically stirred for 70 minutes and ground evenly to form a precursor material;
[0049] 2) freeze-drying the solution in step 1) at -30°C for 18 hours to obtain a precursor powder;
[0050] 3) Pre-carbonization: pre-carbonize the precursor powder in step 2) at 400°C, with a heating rate of 5°C / min and keep warm for 1h;
[0051] 4) Pickling and drying: The material in step 3) is pickled, washed with water, and dried in an oven at 80°C for 10 hours.
[0052] 5) Carbonization: The material pre-carbonized in step 4) is subjected to high-temperature carbonization at 1400° C., with a heating rate of 5° C. / min, kept at this temperature for 2 h, and then cooled to room temperature to obtain a hard carbon negative electrode material.
[0053] Embodiment 2:
[0054] A preparation process of a hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0055] 1) Precursor mixing: zinc gluconate and starch are dispersed and mixed in an aqueous solution in a mass ratio of 1:1, and magnetically stirred for 50 minutes and ground evenly to form a precursor material;
[0056] 2) freeze-drying the solution in step 1) at -15°C for 24 hours to obtain a precursor powder;
[0057] 3) Pre-carbonization: pre-carbonize the precursor in step 2) at 500°C, with a heating rate of 5°C / min and keep warm for 1h;
[0058] 4) Pickling and drying: The material in step 3) is pickled, washed with water, and dried in an oven at 100°C for 8 hours.
[0059] 5) Carbonization: The material pre-carbonized in step 4) is subjected to high-temperature carbonization at 1200° C., with a heating rate of 5° C. / min, and kept at this temperature for 2 h, and then cooled to room temperature to obtain a hard carbon negative electrode material;
[0060] Embodiment 3:
[0061] A preparation process of a hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0062] 1) Precursor mixing: zinc citrate and starch are dispersed and mixed in an aqueous solution in a mass ratio of 1:2, and magnetically stirred for 120 minutes and ground evenly to form a precursor material;
[0063] 2) freeze-drying the solution in step 1) at -30°C for 15 h to obtain a precursor powder;
[0064] 3) Pre-carbonization: pre-carbonize the precursor in step 2) at 600°C, with a heating rate of 5°C / min and keep warm for 1h;
[0065] 4) Pickling and drying: The material in step 3) is pickled, washed with water, and dried in an oven at 80°C for 10 hours.
[0066] 5) Carbonization: The material pre-carbonized in step 4) is subjected to high-temperature carbonization at 1600°C, with a heating rate of 5°C / min, and kept at this temperature for 2 hours, and then cooled to room temperature to obtain a hard carbon negative electrode material;
[0067] Embodiment 4:
[0068] A preparation process of a hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0069] 1) Precursor mixing: zinc acetate and starch are dispersed and mixed in an aqueous solution in a mass ratio of 1:1, and magnetically stirred for 80 minutes and ground evenly to form a precursor material;
[0070] 2) freeze-drying the solution in step 1) at -40°C for 6 hours to obtain a precursor powder;
[0071] 3) Pre-carbonization: pre-carbonize the precursor in step 2) at 500°C, with a heating rate of 5°C / min and keep warm for 1h;
[0072] 4) Pickling and drying: The material in step 3) is pickled, washed with water, and dried in an oven at 80°C for 10 hours.
[0073] 5) Carbonization: The material pre-carbonized in step 4) is subjected to high-temperature carbonization at 1400°C, with a heating rate of 5°C / min, and kept at this temperature for 2 hours, and then cooled to room temperature to obtain a hard carbon negative electrode material;
[0074] Embodiment 5:
[0075] A preparation process of a hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0076] 1) Precursor mixing: zinc citrate, zinc oxalate and starch are dispersed and mixed in an aqueous solution at a mass ratio of 1:1:2, and magnetically stirred for 100 minutes and ground evenly to form a precursor material;
[0077] 2) freeze-drying the solution in step 1) at -30°C for 18 hours to obtain a precursor powder;
[0078] 3) Pre-carbonization: pre-carbonize the precursor in step 2) at 500°C, with a heating rate of 5°C / min and keep warm for 1h;
[0079] 4) Pickling and drying: The material in step 3) is pickled, washed with water, and dried in an oven at 80°C for 10 hours.
[0080] 5) Carbonization: The material pre-carbonized in step 4) is subjected to high-temperature carbonization at 1400°C, with a heating rate of 5°C / min, and kept at this temperature for 2 hours, and then cooled to room temperature to obtain a hard carbon negative electrode material;
[0081] Embodiment 6:
[0082] A preparation process of a hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0083] 1) Precursor mixing: zinc gluconate, starch and glucose are dispersed and mixed in an aqueous solution in a mass ratio of 1:1:1, and magnetically stirred for 120 minutes and ground evenly to form a precursor material;
[0084] 2) freeze-drying the solution in step 1) at -20°C for 23 hours to obtain a precursor powder;
[0085] 3) Pre-carbonization: pre-carbonize the precursor in step 1) at 400°C, with a heating rate of 5°C / min and keep warm for 1h;
[0086] 4) Pickling and drying: The material in step 3) is pickled, washed with water, and dried in an oven at 80°C for 10 hours.
[0087] 5) Carbonization: The material pre-carbonized in step 4) is subjected to high-temperature carbonization at 1400°C, with a heating rate of 5°C / min, and kept at this temperature for 2 hours, and then cooled to room temperature to obtain a hard carbon negative electrode material;
[0088] Comparative Example 1:
[0089] The steps for preparing the hard carbon material for the negative electrode of the sodium ion battery in this comparative example are basically the same as those in Example 1, except that no zinc salt is added during the preparation process.
[0090] Comparative Example 2:
[0091] The steps for preparing the hard carbon material for the negative electrode of the sodium ion battery in this comparative example are basically the same as those in Example 1, except that the preparation process does not involve acid washing.
[0092] Comparative Example 3:
[0093] The steps for preparing the hard carbon material for the negative electrode of the sodium ion battery in this comparative example are basically the same as those in Example 1, except that no zinc salt is mixed, no pre-carbonization treatment is performed, and no acid washing is performed.
[0094] Performance Testing
[0095] The hard carbon negative electrode materials prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were assembled into sodium ion batteries for electrochemical performance testing. The hard carbon material, sodium alginate (SA), and conductive agent (SuperP) were mixed in a mass percentage of 85:5:10, coated on aluminum foil, and dried as the battery positive electrode, metallic sodium was the battery negative electrode, glass fiber was the battery separator, and NaPF6 dimethyl ether (DME) solution was the electrolyte.
[0096] After the battery was assembled, it was left to stand for 8 hours and then subjected to charge and discharge tests. The voltage window was 0.005-3.0V. The charge and discharge tests were completed at a current density of 25mA / g. The results are shown in the following table.
[0097] Material Name Reversible capacity (mAh / g) First effect (%) Example 1 361.1 91.2 Example 2 332.0 83.2 Example 3 350.6 89.1 Example 4 346.5 86.3 Example 5 349.3 85.5 Example 6 352.6 86.3 Comparative Example 1 318.5 85.5 Comparative Example 2 322.2 84.9 Comparative Example 3 310.1 82.6
[0098] According to the test results of Example 1 and Comparative Example 1, the first charge and discharge reversible capacity of the hard carbon negative electrode material in Example 1 can reach 361.1 mAh / g, and the coulombic efficiency can reach 91.2%. The first discharge capacity of the hard carbon negative electrode obtained in Comparative Example 1 can reach 318 mAh / g, and the coulombic efficiency is 85.5%. This shows that the addition of zinc salt can improve the sodium storage capacity of hard carbon. This is because zinc salt generates carbon material and zinc oxide during the pyrolysis process, and nano zinc oxide is evenly embedded in the carbon matrix, which inhibits the foaming of starch, improves the carbon yield of starch, regulates the internal pore structure of starch-based hard carbon, promotes the rearrangement and fixation of carbon materials during pyrolysis, retains a large interlayer spacing, and makes starch-based hard carbon have more micropores and closed-cell structures and small surface defects, while improving the sodium storage capacity and the first efficiency.
[0099] Through the test results of Comparative Example 2 and Comparative Example 3, it can be found that the pre-carbonization strategy can improve the sodium storage capacity and first coulomb efficiency of starch-based hard carbon. This is because zinc oxide is introduced in the pre-carbonization process. These nano zinc oxide particles are embedded in the skeleton structure of the starch carbon material, which inhibits the foaming of the starch and finally obtains a hard carbon precursor with improved sodium storage performance.
[0100] Through the test results of Example 1, Comparative Example 2, Comparative Example 3, etc., it can be found that after pre-carbonization, acid washing to remove zinc oxide, and then high-temperature carbonization can effectively improve the sodium storage performance of starch hard carbon. This is because the zinc oxide generated during the pre-carbonization process plays a pore-forming role, reducing the damage caused by the pyrolysis stage to the newly formed internal carbon-oxygen skeleton structure. Therefore, the pre-carbonized starch treated by this method will maintain a better internal group structure and obtain hard carbon particles with fewer defects.
Claims
1. A process for preparing a hard carbon negative electrode material for a sodium ion battery, characterized in that: The following steps are involved: 1) preparing a precursor mixed solution; 2) drying the solution in step 1) to obtain a precursor powder; 3) Pre-carbonization: pre-carbonizing the precursor powder in step 2) at a medium to low temperature; 4) Pickling and drying: pickling, washing and drying the material in step 3); 5) Carbonization: The material pre-carbonized in step 4) is carbonized at high temperature and then cooled to room temperature to obtain a hard carbon material.
2. The process for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: The step 1) includes: uniformly mixing organic acid zinc salt and polysaccharide biomass to form a precursor material, mixing and dispersing the mixture uniformly, wherein the carbon source of the organic acid salt includes any one or more of zinc citrate, zinc oxalate, zinc gluconate, zinc acetate and zinc lactate.
3. The process for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 2, characterized in that: The mixing is carried out in the form of aqueous solution dispersion, and the aqueous solution dispersion includes magnetic stirring for 30 to 120 minutes; the polysaccharide biomass includes starch or glucose.
4. The process for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: The drying method used in the step 2) includes one or more of freeze drying, spray drying, and thermal evaporation, and the drying time is 6 to 24 hours. Freeze drying includes freeze drying at -40 to -15°C for 11 to 30 hours. The pre-carbonization temperature in the step 3) is 400 to 1000°C, the heating rate is 0.5 to 5°C / min, and the carbonization time is 0.5 to 2 hours.
5. The process for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: The pickling solution in step 4) is one or more of hydrochloric acid, sulfuric acid and nitric acid, with a concentration of 0.05 to 1 mol / L, and the pickling time is 0.5 to 2 hours.
6. The process for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: The atmosphere in the high-temperature carbonization in step 5) is argon, the carbonization temperature is 1000-1800° C., the heating rate is 0.5-10° C. / min, and the insulation time is 1-10 h.
7. The process for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In the step 4), the mixture is dried at 90-120° C. for 6-11 hours.
8. The process for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 2, characterized in that: The mixing ratio of the organic acid zinc salt to the polysaccharide biomass is 1:1-4.
9. A hard carbon negative electrode material for a sodium ion battery, characterized in that: It is prepared by the preparation process described in any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: Including the sodium ion battery hard carbon negative electrode material as described in claim 9.
Citation Information
Patent Citations
Preparation method of high-capacity asphalt-based hard carbon sodium ion battery negative electrode material
CN116969442A
Cited By
Carbon-based negative electrode material and preparation method thereof, sodium-ion battery and electric equipment
CN120573679A